Biomimetic Nanomaterial Strategies for Virus Targeting: Antiviral Therapies and Vaccines. (4th November 2020) - Jackman, Joshua A.; Yoon, Bo Kyeong; Ouyang, Lei; Wang, Nan; Ferhan, Abdul Rahim; Kim, Jaeyun; Majima, Tetsuro; Cho, Nam‐Joon
Abstract: The ongoing coronavirus disease 2019 (COVID‐19) pandemic highlights the importance of developing effective virus targeting strategies to treat and prevent viral infections. Since virus particles are nanoscale entities, nanomaterial design strategies are ideally suited to create advanced materials that can interact with and mimic virus particles. In this progress report, the latest advances in biomimetic nanomaterials are critically discussed for combating viral infections, including in the areas of nanomaterial‐enhanced viral replication inhibitors, biomimetic virus particle capture schemes, and nanoparticle vaccines. Particular focus is placed on nanomaterial design concepts and material innovations that can be readily developed to thwart future viral threats. Pertinent nanomaterial examples from the COVID‐19 situation are also covered along with discussion of human clinical trial efforts underway that might lead to next‐generation antiviral therapies and vaccines. Abstract : Biomimetic nanomaterials have excellent potential to combat viral infections and lay the groundwork for next‐generation antiviral therapies and vaccines. There is ongoing progress to develop nanomaterial‐enhanced viral replication inhibitors, virus‐binding nanoparticles, and nanoparticle vaccines, some of which are currently in human clinical trials and might be useful to stop the ongoing 2019 coronavirus disease pandemic along with future viral threats.